2007
DOI: 10.1897/07-381
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Hazard Assessment of Polychlorinated Biphenyls, Polybrominated Diphenyl Ethers and Polychlorinated Dibenzo-p-Dioxins and Dibenzofurans to Yangtze Finless Porpoise in Dongting Lake, China

Abstract: Abstract-Yangtze finless porpoise (Neophocaena phocaenoides asiaeorientalis), a protected endangered species, is the sole freshwater subspecies of finless porpoise, living only in the middle and lower reaches of the Yangtze River, China, and its appended lakes. Its population has decreased sharply to 1,400 because of human activities, including environmental contamination. In the present study, polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs), and polychlorinated dibenzo-p-dioxins and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Yang et al (2008) determined PBDEs in blubber, liver, kidney, stomach, small intestine, and brain tissues of five Yangtze finless porpoise (Neophocaena phocaenoides asiaeorientalis). This specie is the sole freshwater subspecies of finless porpoise, living only in the middle and the lower reaches of the Yangtze River, China, and its appended lakes.…”
Section: Aquatic Mammalsmentioning
confidence: 99%
“…Yang et al (2008) determined PBDEs in blubber, liver, kidney, stomach, small intestine, and brain tissues of five Yangtze finless porpoise (Neophocaena phocaenoides asiaeorientalis). This specie is the sole freshwater subspecies of finless porpoise, living only in the middle and the lower reaches of the Yangtze River, China, and its appended lakes.…”
Section: Aquatic Mammalsmentioning
confidence: 99%
“…This decline is being driven by high levels of mortality resulting from anthropogenic impacts such as incidental by-catch in legal and illegal fishing gear, ship collisions, widespread sand dredging, pollution, and water development projects along the middle and lower reaches of the Yangtze River (Wang et al, 2000Yang et al, 2002Yang et al, , 2008aXia et al, 2005;Zheng et al, 2005;Zhao et al, 2008;Wang, 2009). The Yangtze is known as the ''golden channel'' of central China, and supports the livelihoods of hundreds of millions of people through agriculture, aquaculture and industrial activities.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study of Yang et al (2008) found PCB concentrations in Yangtze finless porpoises, a protected endangered species of freshwater finless porpoise living in the middle and lower reaches of the Yangtze River were 0.06-1.89 lg g À1 lipid. The PCB concentrations in the porpoise were only comparable or even lower than those in some cetaceans studied previously.…”
mentioning
confidence: 99%